2007
DOI: 10.1111/j.1464-410x.2007.06908.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of p53, Ki‐67, epithelial cadherin and matrix metalloproteinase‐9 in penile squamous cell carcinoma treated with surgery

Abstract: OBJECTIVE To evaluate the prognostic significance of p53, Ki‐67, epithelial cadherin (E‐cadherin) and matrix metalloproteinase‐9 in primary penile cancer, as the presence of lymph node metastasis and long‐term survival are hard to define in penile squamous cell carcinoma. PATIENTS AND METHODS Paraffin‐embedded primary tumour samples were obtained from 73 Chinese patients who had penile amputation and regional lymphadenectomy. The expression of molecular markers was determined by immunohistochemistry. Logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 28 publications
4
37
2
Order By: Relevance
“…A 30% cutoff was selected because the results of exploratory analysis showed no advantages for quartile ratios of 10, 20, or ≥ 40%. The expression of p53 and Ki-67 was determined by immunohistochemistry similar to our previous study [10]. After operation, a CT scan of the groin basin was taken every 2-3 months.…”
Section: Methodsmentioning
confidence: 99%
“…A 30% cutoff was selected because the results of exploratory analysis showed no advantages for quartile ratios of 10, 20, or ≥ 40%. The expression of p53 and Ki-67 was determined by immunohistochemistry similar to our previous study [10]. After operation, a CT scan of the groin basin was taken every 2-3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have observed that p53 protein correlates with node involvement and prognosis [9,10]. Ficarra et al [11], using a multicenter database of 265 patients, devised a nomogram to predict the probability of inguinal node involvement that takes into account clinical and pathologic variables using multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We asked for the patients' consent for the invasive procedure only when they had cutaneous metastases which can be easily obtained with little damage. The expressions of Ki-67 and CD34 were evaluated by immunohistochemical techniques which have been described in a previous report [14] . Monoclonal antibodies used were clone MIB-1 (anti-Ki-67, at 1: 75 dilution, Dakocytomation, Glostrup, Denmark) and clone QBEnd-10 (anti-CD34, at 1: 40 dilution, Dakocytomation).…”
Section: Methodsmentioning
confidence: 99%